Early Marriage in Natuna Regency, Riau Archipelago Province in the Perspective of Legal Sociology - Adiya Pepriyana; Laila Fitriani; Novita Anggrainy (Formosa Journal of Science and Technology, 2023)
This research study aims to analyze the reasons for the increasing number of cases of early marriage in Natuna using social control theory, the impact that will arise as a result of early marriage and the efforts that can be made to control early marriage in Natuna. The research method used in this study is a literature study which is carried out by examining sources obtained from books, journals, as well as sources generated from internet news or using secondary data. It was found that the high rate of early marriage in Natuna was caused by a lack of parental control over children so that children carried out negative behaviors, namely getting pregnant out of wedlock. In the case of early marriages in Natuna, socialization has been carried out in schools but there is still an increase in early marriages in Natuna due to arranged marriages by parents, economy and socio-culture. Then the research obstacle was due to the method of writing a literature study, it was very difficult to add interviews and more recent information from local residents.